Analysis of diversity among cumin (Cuminum cyminum) cultivars using RAPD markers - CHOUDHARY, SHARDA; MEENA, R S; SINGH, R; VISHAL, M K; JETHRA, GEETIKA; SAINI, MAMTA; PANWAR, ALKA (The Indian Journal of Agricultural Sciences, 2015)
Cumin (Cuminum cyminum) is a valuable seed spice belonging to the family apiaceae. It is one of the oldest and economically most important seed spice with medicinal properties. In the present study, experiments were conducted to assess the genetic diversity among Indian cumin, accessions by using RAPD molecular markers. After DNA extraction, complement gene locuses were amplified by 20 RAPD primers, out of which only 15 primers showed amplification. These primers produced 1191 bands, of which 218 bands (about 18.30%) were polymorphic. This indicates very low level of genetic diversity among genotypes. Cluster analysis was performed using UPGMA method and Dice’s similarity coefficient by NTSYS software. The resulting dendrogram categorized the accessions into three groups showing 53% similarity. Principle Component Analysis was performed and 3 dimensions graphs using 15 primers and 55 genotypes were drawn.